Experiment and simulation study on the optimization of the PV direct-coupled solar water heating system. (1st April 2016) - Wang, Yanqiu; Ji, Jie; Sun, Wei; Yuan, Weiqi; Cai, Jingyong; Guo, Chao; He, Wei
Abstract: Most solar water heating systems (SWHS) are forced circulation systems using AC pumps. Controlled by an ON/OFF differential temperature sensing controller, the heat transfer fluid in a SWHS flows at a constant rate, and the controller consumes electricity. The controller and the sensors lead to system malfunctions, and AC pumps cycle between ON and OFF frequently under low solar irradiance. Hence, PV direct-coupled DC pumps are promising in SWHS, since they are simple and reliable. In this study, an optimization study of a PV direct-coupled SWHS (PV-SWHS) which uses a PV direct-coupled DC pump to circulate the heat transfer fluid is presented. A system model is built and validated with experiments. Two different types of PV module designs are investigated. The performance of the PV-SWHS under different real weather conditions is studied and compared with the performance of the conventional SWHS. And an optimum design method of PV-SWHS is proposed. The results show that: (i) the startup solar irradiance of the pump is the major factor which affects the thermal efficiency of PV-SWHS; (ii) a proper PV module design can reduce the requirement of PV cells by more than 25%; (iii) the PV-SWHS can work well without circulation controller; (iv) the optimized PV-SWHS has nearly the same thermal efficiency and better long-term system reliability than the conventional SWHS. Therefore, the PV-SWHS is very promising. Highlights: Experiments and simulations on the PV direct-coupled solar water heating system (PV-SWHS) are conducted. The major parameters which affect the performance of PV-SWHS are investigated. An optimization design method of the PV-SWHS is proposed. A comparison of PV-SWHS and the conventional SWHS is conducted.